PENYUSUNAN STANDARD OPERATING PROCEDURE (SOP) PEMELIHARAAN INFRASTRUKTUR PADA POLITEKNIK NEGERI KETAPANG - Faisal, Muhammad Hanif; Alwi, Abu Bakar (Fakultas Teknik Universitas Tanjungpura, 2017)
In the early stages of the process of implementing a maintenance program, it is the policy of the building owner to desire to maintain the building in order to create a comfortable and safe feeling for its users. Without the commitment of the building owner, the maintenance program will not run smoothly. The next stage related to policy is to develop a framework for maintenance programs, design maintenance programs and strategic design maintenance programs. At this stage the concentration selection will take place, of course, adjusted to the focus of the building designation. Next is to apply all the programs that have been agreed on to the building and its facilities, including the filling out of the forms that must be filled in by the implementers of this program.A Standard Operating Procedure (SOP) is a set of written instructions that document a routine or repetitive activity followed by an organization. The development and use of SOPs are an integral part of a successful quality system as it provides individuals with the information to perform a job properly, and facilitates consistency in the quality and integrity of a product or end-result. Well-written SOPs should first briefly describe the purpose of the work or process, including any regulatory information or standards that are appropriate to the SOP process, and the scope to indicate what is covered. SOPs may be written for any repetitive technical activity, as well as for any administrative or functional programmatic procedure, that is being followed within an organization